Types of Media in Arabic Language Learning - Raudatul Firdausinnisa; Julkarnain; Abdul Azis (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Learning media is one of the components in learning apart from learning objectives, materials, educators and students, methods and assessment. Good learning media is adapted to developments in science and technology. Based on these developments, learning media is needed that can attract students' attention in learning. As in learning Arabic, one type of media used is audiovisual media based on language learning videos and applications that can support the learning process. The study in this article uses a qualitative research method based on library research with data collection techniques using documentation techniques. The results of this research discuss the types of media used in Arabic language learning, namely audiovisual media and online learning videos as Arabic language learning media and their advantages and limitations, and Arabic language learning applications and the advantages and limitations of using applications as learning media. Arabic